2016
DOI: 10.1016/j.ebiom.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Incidentalome from Genomic Sequencing: A Barrier to Personalized Medicine?

Abstract: BackgroundIn Western cohorts, the prevalence of incidental findings (IFs) or incidentalome, referring to variants in genes that are unrelated to the patient's primary condition, is between 0.86% and 8.8%. However, data on prevalence and type of IFs in Asian population is lacking.MethodsIn 2 cohorts of individuals with genomic sequencing performed in Singapore (total n = 377), we extracted and annotated variants in the 56 ACMG-recommended genes and filtered these variants based on the level of pathogenicity. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
2
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 43 publications
0
32
2
4
Order By: Relevance
“…To foster such discussions, knowledge on the prevalence of secondary findings in medically actionable genes in the general population is required. Recently, multiple studies have reported frequencies of secondary findings ranging from 1 to 9% in various populations [5][6][7][8][9][10][11][12][13]. This broad range of reported frequencies is largely explained by the cohorts tested (e.g., inclusion of individuals more prone to have a pathogenic variant) in combination with differences in sequence technology (e.g., whole-exome sequencing (WES) of inferior quality), classification of variants, and amount of genes for which pathogenic variants are taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…To foster such discussions, knowledge on the prevalence of secondary findings in medically actionable genes in the general population is required. Recently, multiple studies have reported frequencies of secondary findings ranging from 1 to 9% in various populations [5][6][7][8][9][10][11][12][13]. This broad range of reported frequencies is largely explained by the cohorts tested (e.g., inclusion of individuals more prone to have a pathogenic variant) in combination with differences in sequence technology (e.g., whole-exome sequencing (WES) of inferior quality), classification of variants, and amount of genes for which pathogenic variants are taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of ACMG cancer gene LP/P variants in our increased FH risk group was also considerably higher than other reported studies that assessed the presence of pathogenic variants in the 59 ACMG gene list of unselected populations ranging from 1.5% 27 to 2.7% 7 and 1.6% in an ethnically similar cohort. 28 Large scale population screening programs have been initiated globally to optimise the utility of genomic data. The analysis of genomic data has unquestionably led to a greater understanding of the genetic basis of health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…Accuracy of the finding from GWASs needs to be replicated and confirmed. This is partly due to high prevalence of incidental findings or incidentalome, referring to identifying variants in genes that are unrelated to the patient's primary condition (Brothers et al, 2013;Jamuar et al, 2016).…”
Section: Looking Ahead and Future Perspectivesmentioning
confidence: 99%